Subjective Norm of Interest to Use in Online Shopping - Rini Larasati Irawan; Ratih Hurriyati; Mohamad Reza Nurpratama (Almana : Jurnal Manajemen dan Bisnis, 2020)
In this generation, shopping online is not considered a taboo thing anymore. This matter is supported by its various applications that are already familiar to people all over the world. Jakarta is among one of all Indonesian capital cities, where shopping online has made it easier for people to shop and to erase gaps while shopping, saves more time, and it's other advantages. The urge and influence of people around us can be one of the main reasons that might affect it. Subjective norm and interest to use are the two variables used in this research. The data were collected by spreading questionnaires through google forms, the amount of collected respondent are 65 respondent who came from Jakarta. The result of the research used the AMOS program. And the hypothesis test result shows that all probabilities, whether it's the subjective norm or the interest to use, are significant.